2020
DOI: 10.1136/bmjopen-2019-036055
|View full text |Cite
|
Sign up to set email alerts
|

Is dual use of nicotine products and cigarettes associated with smoking reduction and cessation behaviours? A prospective study in England

Abstract: ObjectivesTo investigate associations of dual use of e-cigarettes and cigarettes with subsequent quitting activity (smoking reduction, quit attempts and use of evidence-based cessation aids). To overcome potential confounding by factors associated with use of pharmacological support, we selected dual use of over-the-counter nicotine replacement therapy (OTC NRT) and cigarettes as a behavioural control.DesignProspective cohort study with 6-month follow-up.SettingEngland, 2014–2016.Participants413 current smoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Our findings align with some aforementioned studies that have not found e-cigarette use to be associated with depressed uptake of behavioural support [ 26 , 27 ]. Conversely, an English study found in an unplanned analysis that dual users of tobacco/e-cigarettes were significantly less likely than dual users of tobacco/NRT to specifically use behavioural support or prescription medication, though the two groups did not differ in their overall use of evidence-based cessation aids [ 25 ]. This mixed evidence base could result from differences in study designs, since Beard et al employed a prospective cohort design [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings align with some aforementioned studies that have not found e-cigarette use to be associated with depressed uptake of behavioural support [ 26 , 27 ]. Conversely, an English study found in an unplanned analysis that dual users of tobacco/e-cigarettes were significantly less likely than dual users of tobacco/NRT to specifically use behavioural support or prescription medication, though the two groups did not differ in their overall use of evidence-based cessation aids [ 25 ]. This mixed evidence base could result from differences in study designs, since Beard et al employed a prospective cohort design [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research has only recently begun to explore whether vaping amongst smokers may be specifically affecting behavioural support uptake, with mixed findings. A recent UK prospective study suggested that, amongst smokers making a “serious quit attempt”, use of e-cigarettes was associated with reduced likelihood of specifically using behavioural support or prescription medication [ 25 ]. Although conclusions that can be drawn from cross-sectional or ecological research are more limited, available studies have found different results.…”
Section: Introductionmentioning
confidence: 99%
“…We included in our models a range of variables measured at Wave 1 identified in the literature ( Jackson et al, 2020 ) as potential confounders in the association between dual use (of e-cigarettes and cigarettes) and cessation. Sociodemographic covariates included age [18–24 (reference), 25–34, 35–44, 44–54, 55 + ]; sex [male and female (reference)], race/ethnicity [Non-Hispanic White (reference), Non-Hispanic Black, Non-Hispanic Other and Hispanic]; education [high school or less (reference), some college and bachelor’s degree or higher]; income [< $25,000 (reference), $25,000-$49,999, ≥$50,000 and not reported]; census region [Northwest (reference), Midwest, South, and West].…”
Section: Methodsmentioning
confidence: 99%
“…For binary outcome data we will use as binary and multivariable binary logistic (for odds ratios) or log-binomial (for relative risks) regression. These methods have been employed in numerous STS studies to analyse associations between self-reported abstinence and use of different smoking cessation aids 32 , 33 . Where the outcomes are ordinal or have more than two levels we will use ordinal or multinomial logistic regression, respectively.…”
Section: Methodsmentioning
confidence: 99%